Synthesis, Biological Evaluation and Molecular Docking Studies of Novel Di-hydropyridine Analogs as Potent Antioxidants - Sudhana, Saddala M.; Adi, Pradeepkiran Jangampalli (Current Topics in Medicinal Chemistry, 2019)
Aim: The aim of this study is to synthesize, characterize and biological evaluation of 3-ethyl 5- methyl2-(2-aminoethoxy)-4-(2-chlorophenyl)-1,4-dihydropyridine-3,5-dicarboxylate derivatives. Background: An efficient synthesis of two series of novel carbamate and sulfonamide derivatives of amlodipine, 3-ethyl 5-methyl 2-(2-aminoethoxy)-4-(2-chlorophenyl)-1,4-dihydropyridine-3,5-dicarboxylate (amlodipine) 1 were chemical synthesized process. Materials & Methods: In this process, various chloroformates 2(a-e) and sulfonyl chlorides 4(a-e) on reaction with 1 in the presence of N,N–dimethylpiperazine as a base in THF at 50-550 oC, the corresponding title compounds 3(a-e) and 5(a-e) in high yields. Furthermore, the compounds 3(a-e) and 5(a-e) were evaluated for antioxidant activity (DPPH method), metal chelating activity, hemolytic activity, antioxidant assay (ABTS method), cytotoxicity, molecular docking and in silico ADMET properties. Results: Results revealed that 5a, 5e, 3d, 3a and 5c exhibited high antioxidant, metal chelating activities, but 5a, 5e and 3d exhibited low activity. The molecular docking studies and ADMET of suggested ligands showed the best binding energies and non-toxic properties. Conclusion: The present in silico and in vitro evaluations suggested that these dihydropyridine derivatives act as potent antioxidants and chelating agents which may be useful in treating metals induced oxidative stress associated diseases.
Keywords: Potent antioxidant